The dynamics of Polish labour market - M Balcerowicz-Szkutnik (RUDN Journal of Economics, 2011)
The article presents the results of the analyses concerning the parameters of Polish labour market for the years 1998-2009. A special attention was given to the coefficients of occupational activity, employment rates and the level of both general and long-term unemployment. The analyses were performed separately for the gender of employees and with the consideration of the territorial division, while separating voivodeships with the lowest and the highest rates. It has been observed that the dynamics of changes on Polish labour market is closely associated with the changing age structure of the population and has specific consequences in the sphere of condition of Polish pension scheme and social security system. The conclusions emphasise the fact that the level of coefficients that characterise the Polish labour market is the most unfavourable in marginal age brackets of people that make labour resources. During 2004-2009 have been distinguished from the period of 1998-2003, because at that time the change of parameters that characterise Polish labour market was clearly apparent. It was associated with accession of Poland to the EU.